About the Risks of Developmental Disorders in Early Life and Their Prevention - Kholodova, O.L.; Kuzmenko, M.Yu; Arbekova, O.A. (Sovremennaâ Zarubežnaâ Psihologiâ, 2024)
The article shows the foreign experience of the approach to creating conditions for the development of an early age child, including children with disabilities. The factors of early childhood development, as well as the risks for development and their prevention are considered. Using the example of successful practices, it is discussed what educational conditions are to be created for the development of toddlers, especially for social and emotional development in groups of young children, including integration formats to promote the child's own research activity, free play and movement, interaction with other children and adults. Special attention is paid to the prevention of the risks of developmental disorders, the peculiarities of working with children with disabilities, the role of the teacher and his/her interaction with the child in the group - the style of communication, the use of speech, the peculiarities of assistance and support to the child's own activity and the development of his/her selfdependence. The principal trends of the modern approach to creating conditions in the group for the development of young children in foreign practice are highlighted: the importance of the quality of interaction, scaffolding, the creation of a subject-based developing environment, the synthesis of achievements of various psychological and pedagogical theories, the attitude to dialogue and cooperation with parents, the possibility of inclusion. In terms of creating conditions for children with disabilities and early intervention, individual classes are more often used, less frequently group classes, the format of integrative groups with typically developing children is promising, while active interaction and cooperation with parents is important. The principal trends of the modern approach to creating conditions in the group for the development of young children in foreign practice are highlighted: the importance of the quality of interaction, scaffolding, the creation of a subject-based developing environment, the synthesis of achievements of various psychological and pedagogical theories, the attitude to dialogue and cooperation with parents, the possibility of inclusion. In terms of creating conditions for children with disabilities and early intervention, individual classes are more often used, less often group classes, the format of integrative groups with normotypically developing children is promising, while active interaction and cooperation with parents is important. В статье показан зарубежный опыт подхода к созданию условий для развития ребенка раннего возраста, включая детей с ограниченными возможностями здоровья. Рассматриваются факторы развития ребенка раннего возраста, а также риски для развития и их профилактика. На примере успешных практик обсуждается, какие образовательные условия важно создавать для развития малыша, особенно для социального и эмоционального развития в группах детей раннего возраста, включая интеграционные форматы, чтобы способствовать собственной исследовательской активности ребенка, свободной игре и движению, взаимодействию с другими детьми и взрослыми. Особое внимание уделяется профилактике рисков нарушений развития, особенностям работы с детьми с ограниченными возможностями здоровья, роли педагога и его взаимодействию с ребенком в группе - стилю общения, использованию речи, особенностям оказания помощи и сопровождения для поддержки собственной активности ребенка и развития его самостоятельности. Выделены принципиальные тенденции современного подхода к созданию условий в группе для развития детей раннего возраста в зарубежной практике: обеспечение качества взаимодействия, скаффолдинг, создание предметной развивающей среды, синтез достижений разных психолого-педагогических теорий, установка на диалог и сотрудничество с родителями, возможность инклюзии. В аспекте создания условий для детей с ограниченными возможностями здоровья и раннего вмешательства чаще используются индивидуальные, реже - групповые занятия, перспективным является формат интегративных групп с нормотипично развивающимися детьми, при этом важно активное взаимодействие и сотрудничество с родителями.